Demography and radial growth accumulation of an endemic and threatened tree species from the Southern Plateau of Santa Catarina - Higuchi, Pedro (2024)
Cloud mountain forests are important ecosystems because of their high endemism of species and essential ecosystem functions, but they are highly threatened by climate change. Crinodendron brasiliensis is an endemic tree of the Serra Geral and is currently classified as threatened with extinction. This study investigated the demographic dynamics and growth pattern of Crinodendron brasiliense in its natural habitat. The study was conducted in two cloud forest areas in São Joaquim National Park in Urubici, Santa Catarina. For the study of demographic dynamics, individuals (dbh > 5 cm) were sampled in 20 plots of 10x10 distributed in a transect (20x100m). Demographic rates of mortality, recruitment, basal area gain and loss, net change, and turnover were evaluated. For the growth study, automatic radial dendrometers were attached to five individuals in another cloud forest fragment. A thermo-hygrometer was installed to monitor air temperature in an adjacent open area. In general, demographic dynamics can be summarized by the net change in the number of individuals (-1,94%.ano-1) and basal area stability (-0,06%.ano-1) . Dendrometers indicated low cumulative growth, with growth concentrated in January through March. It can be concluded that the observed individuals have low growth, are affected by temperature, and are in a phase of self-thinning.